2019
DOI: 10.1308/rcsann.2019.0063
|View full text |Cite
|
Sign up to set email alerts
|

Use of an automated knot fastener shortens operative times in minimally invasive mitral valve repair

Abstract: Introduction Longer durations of cardiopulmonary bypass and aortic cross clamp are associated with increased morbidity and mortality. Little is known about the effect of automated knot fasteners (Cor-Knot®) in minimally invasive mitral valve repair on operative times and outcomes. The aim of this study was to evaluate whether these devices shortened cardiopulmonary bypass and aortic cross clamp times and whether this impacted on postoperative outcomes. Materials and methods All patients undergoing isolated min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 10 publications
1
26
0
Order By: Relevance
“…Whilst the patients in the studies from this review had on average good ventricular function, the reduction in CPB and AXT offered by Cor‐Knot makes it particularly applicable for patients with a poor ventricular function who are otherwise high‐risk for valvular surgery . Despite this, we did not find evidence that the application of Cor‐Knot confers improved clinical outcomes, including an equivalence in the length of total in‐hospital stay and ICU stay . On the other hand, the lack of power in the studies may be the reason why an improved patient outcome conferred by Cor‐Knot is yet to be detected …”
Section: Discussionmentioning
confidence: 68%
“…Whilst the patients in the studies from this review had on average good ventricular function, the reduction in CPB and AXT offered by Cor‐Knot makes it particularly applicable for patients with a poor ventricular function who are otherwise high‐risk for valvular surgery . Despite this, we did not find evidence that the application of Cor‐Knot confers improved clinical outcomes, including an equivalence in the length of total in‐hospital stay and ICU stay . On the other hand, the lack of power in the studies may be the reason why an improved patient outcome conferred by Cor‐Knot is yet to be detected …”
Section: Discussionmentioning
confidence: 68%
“…7 It functions as an alternative to the more conventionally employed endoscopic knot pusher, the use of which is more time consuming, has greater inter-user variability, and is prone to producing loose ('air') knots (whose correction often prolongs operations). 19 Cor-Knot essentially eliminates these pitfalls whilst also reducing the time taken to fasten and trim sutures. It is most commonly employed in aortic valve replacement (AVR) and mitral valve (MV) repair.…”
Section: Indications Benefits and Shortcomings Of Cor-knotmentioning
confidence: 99%
“…11,33 With respect to CPBT and AXT, four of the five studies independently found these times to be reduced by Cor-Knot, a finding that was further supported by a meta-analysis. 6,11,19,27,33,34 30 -RCT Perin et al 9 -PCS Wang et al 9 -RCS Morgant et al 10 -PCS Length of ICU stay No significant difference Lee et al 30 -RCT No significant difference Grapow et al 11 -RCS Plestis et al 24 -RCS Perin et al 19 -PCS Beute et al 32 -RCS Morgant et al 10 -PCS Abbreviations: AXT, aortic cross clamp time; AVR, aortic valve replacement; CPBT, cardiopulmonary bypass time; ICU, intensive care unit; MA, meta-analysis; MV, mitral valve; PCS, prospective cohort study; PPI, permanent pacemaker implantation; PVL, paravalvular leak; RCS, retrospective cohort study; RCT, randomized controlled trial.…”
Section: Cor-knot In Mitral Valve Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…The CORKNOT® device is an automated titanium suture fastening system used predominantly in minimally invasive cardiac surgery. The CORKNOT® device has been reputed for its bene ts in terms of strength, security and reliability 1,2 . It is an ergonomic device that allows automatic crimping and trimming of sutures with a single squeeze.…”
Section: Introductionmentioning
confidence: 99%